Russka - Rutherfurd, Edward (London Century, 2012)
The triumphs, tragedies, passions, and struggles of successive generations of four families are shaped by the turbulent events and forces of Russian history. Spanning 1800 years of Russia's history, people, politics, and culture, this novel tells a grand saga that is as multifaceted as Russia itself.
Keywords: Russia (Federation) -- Soviet Union -- Historical fiction